Effect of TID electronradiation on SiGe BiCMOS LNAs at V-band. (September 2020) - Sagouo Minko, Flavien; Stander, Tinus
Abstract: We investigate the effect of TID electron irradiation on a 65 GHz LNA in 130 nm SiGe BiCMOS. The LNA is exposed to a Sr-90 radiation source and irradiated at a rate of 200 krad (Si)/hr to a total dose of 15 Mrad (Si), with S-parameter and NF measurements taken at regular intervals. It is found that TID produces and increase in the input impedance, especially in the reactive component. The damage results in 2.3 dB reduction in midband gain, 2.97 dB increase in midband NF and up to 8.19 dB increase in midband S11, although the device remains matched across the band of interest. The degradation is found most pronounced at the band-edges, yielding a 1 dB gain flatness bandwidth reduction of 32%.